Numerical Analysis and Diagnosis of the Hydrodynamic Effects Produced by Hurricane Gordon along the Coast of Spain - Díaz Hernández, Gabriel; Méndez Incera, Fernando Javier; Mínguez Solana, Roberto (Weather and Forecasting, 2014)
This paper presents a detailed hindcast for the generation and propagation of sea state variables—significant wave heightHs, peak period Tp,mean direction u, and spectral shape g –s —associated with cyclonic events to numerically diagnose their possible hydrodynamic effects over the northeastern Atlantic. An example of such cyclonic events is Hurricane Gordon, which occurred during the second half of August 2012. Extreme hurricane-strength winds produced new and atypically low-frequency (about 14 s) packs of energy. The preexistent wave spectrum suddenly experienced an addition of low-frequency energy along the coast of Cadiz, Spain. This study presents the results of a comprehensive analysis developed to reconstruct the events produced by Hurricane Gordon (2012) along the coast of Cadiz. The analysis features the use of (i) parametric models for the characterization of hurricane winds and pressure fields, (ii) implementation of the Simulating Waves Nearshore (SWAN) model for the generation and propagation of waves in the northeast Atlantic Ocean, and (iii) its coupling with theMOPLA—taken fromthe Spanish acronym for wave propagation model, current, and morphodynamic evolution of beaches—model for the evaluation of longshore currents. The numerical wave characterization, generation, and propagation were validated with instrumental data from deep-water and coastal buoys. This work was partially funded by projects ‘‘GRACCIE’’ (SD 2007- 00067, CONSOLIDER INGENIO2010) and ‘‘iMar21’’ (BiA2011-2890) from the Spanish government.